Structure and magnetic properties of highly oriented LaBaCo2O5+δ films deposited on Si wafers with Pt/Ti buffer layer - Shaibo, Jamal; Yang, Rui; Wang, Zhe; He-Ming, Huang; Hui-Kai, He; Qing-Yu, Zhang; Guo, Xin (Physical chemistry chemical physics : PCCP, 2019)
Fabrication of highly crystalline oxide films onto silicon wafers has long been a critical obstacle for integrating multi-functional oxides into silicon-based technology. Herein, Pt/Ti is used as a buffer layer for the integration of highly oriented crystalline LaBaCo2O5+δ (LBCO) thin films onto silicon via pulsed laser deposition. LBCO films are highly (00l) oriented with smooth and sharp LBCO/Pt interfaces. The highly oriented LBCO films exhibit a high magnetic transition temperature (TC) and large coercive field (HC) with superparamagnetism over those deposited on single crystal substrates. What is more, the metallic-like behavior with enhanced magnetoresistance is also observed. The opportunity of using a Pt/Ti buffer layer as the growth template opens an alternative route for integrating functional transition metal oxides with tunable magnetic properties into Si-based technology.